2015
DOI: 10.1007/s10067-015-2999-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety evaluation of a combination of iguratimod and methotrexate therapy for active rheumatoid arthritis patients: a randomized controlled trial

Abstract: This study aimed to investigate the efficacy and safety of iguratimod (T-614) in combination with methotrexate (MTX) for active rheumatoid arthritis (RA) patients. Sixty active RA patients were enrolled according to the 2010 American College of Rheumatology (ACR) and the European League Against Rheumatism (EULAR) classification criteria, and were randomized into MTX + T-614 group and MTX group. T-614 was orally administered at a dosage of 50 mg/day (25 mg twice daily) for 24 weeks. MTX was orally administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Also known as iguratimod, T-614 is currently clinically available in Japan and China as a daily oral formulation administered at 25-50 mg daily, which has shown safety and efficacy in improving symptoms and disease progression in rheumatoid arthritis both as a monotherapy (92)(93)(94) and in combination with methotrexate (95). Several preclinical studies have suggested that the drug may also have utility in other settings, such as multiple sclerosis (62) and cachexia in the context of adenocarcinoma (96).…”
Section: T-614 In Combination With Glucocorticoids Attenuates Diseamentioning
confidence: 99%
“…Also known as iguratimod, T-614 is currently clinically available in Japan and China as a daily oral formulation administered at 25-50 mg daily, which has shown safety and efficacy in improving symptoms and disease progression in rheumatoid arthritis both as a monotherapy (92)(93)(94) and in combination with methotrexate (95). Several preclinical studies have suggested that the drug may also have utility in other settings, such as multiple sclerosis (62) and cachexia in the context of adenocarcinoma (96).…”
Section: T-614 In Combination With Glucocorticoids Attenuates Diseamentioning
confidence: 99%
“…Two 24-week clinical studies both showed similar results. The group of IGU combined with MTX had better outcomes than that of MTX alone, such as Patient's clinical manifestations including joint tenderness and swollen joint count, pain visual analogue scale overall assessment of patients and physicians, ESR, CRP, health assessment questionnaire, DAS28, simplified disease activity index, and ACR 50 (P < 0.05) ( Table 2) (Duan et al, 2015;Xia et al, 2016). Interestingly, there was no significant difference in the incidence of adverse events between the IGU+MTX group and the MTX group (P > 0.05).…”
Section: Igu Combined With Other Drugs Igu Combined With Mtxmentioning
confidence: 99%
“…After subsequent screening, an additional 33 were excluded: 30 randomized controlled trials (RCTs) did not include the ACR20/50/70, 2 RCTs did not report adverse events, and 1 RCT was repeated in more than one bibliographic source. After the selection process, a total of 7 RCTs consisting of 665 participants with 368 participants in the active arm and 297 in the placebo arm were included in the meta-analysis [1,[16][17][18][19][20][21]. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram is included in .…”
Section: Search Resultsmentioning
confidence: 99%
“…Three trials [16][17][18] reported that the primary efficacy endpoint was the rate at which patients (the full analysis set)…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%